Vision of the farmers, professional and students of the agronomic area in respect of soil and water conservation in Londrina, Pr - Tavares, João; Rinschede, Mariana (Semina: Ciências Agrárias, 2009)
The ambient degradation due to bad use of the natural resources and the inadequate techniques of production is a current problem and is being subject of debates among the civil society, government and private initiative that search to formulate solutions and to congregate efforts to diminish the impact and decelerate this process. However, throughout the time the intensified exploration aiming always high productions and great economic returns goes many times in the against-hand of the preservation and conservation of the environmental resources. So, this work was developed with the aim of knowing the interest of farmers, students and Agronomic professionals for the conservation of soil and water. It was concluded that 74% of the interviewed agricultural producers consider necessary to use conservationist's practices in the property and 26% do not see this necessity. However, 31.6% only make use of conservation practices for personal option, against 68.5% that only use riparian forest and reforestation for imposition of the law. In relation to the professionals of the area of Agronomy, 100% of them see necessity in using conservation practices in the agricultural activity, and consider more important: riparian forest (24%), no tillage (15%) and agricultural terrace (6%); however, 39% of the professionals do not see necessity in using agricultural terrace in areas with no tillage. The students of the course of Agronomy of the State University of Londrina, 50% only are in the course for personal option and 50% attend influence of the parents or for other reasons that not it attraction for the profession; and 80% of the students would attend a course on soil an water conservation and 20% would do it if obliged.